Legalitas Transaksi Jual Beli Online dalam Perspektif Fiqih Muamalah - Mardiyah; Chanifudin; Abdul wahab (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Univesitas Muhammadiyah Bengkulu, 2025)
The rapid development of digital technology has given rise to new forms of economic transactions, one of which is online buying and selling conducted through digital platforms and internet networks. This phenomenon raises various legal issues from the perspective of fiqh muamalah, particularly concerning the validity of contracts, fulfillment of the pillars and conditions of sale, and the potential presence of prohibited elements such as gharar, tadlis, and dharar. This article aims to analyze the legality of online buying and selling transactions from the perspective of fiqh muamalah using a normative qualitative approach based on library research. The study finds that online buying and selling transactions are basically permissible in Islamic law as long as they fulfill the pillars and conditions of sale, including the presence of contracting parties, clear objects of contract, offer and acceptance (ijab and qabul), and the absence of prohibited elements. Online sale contracts may be analogized to salam contracts or bai’ al-mu’athah, depending on the transaction mechanism. Thus, online buying and selling has legal validity in fiqh muamalah as long as it is conducted in accordance with the principles of justice, honesty, and public benefit. Keywords: online buying and selling, fiqh muamalah, contract, legal validity.